1993
DOI: 10.1113/expphysiol.1993.sp003716
|View full text |Cite
|
Sign up to set email alerts
|

Volume‐sensitive KCl co‐transport and taurine fluxes in horse red blood cells

Abstract: SUMMARYPotassium (using 86Rb+ as a tracer), amino acid and taurine fluxes were measured in horse red blood cells (RBCs). No volume-sensitive component of alanine and glycine transport was observed, and although volume-sensitive taurine fluxes were observed in most animals, their absolute magnitudes were small. K+ fluxes, however, were shown to be particularly volume sensitive; they were stimulated by cell swelling and inhibited by cell shrinkage. Sizeable fluxes were present at normal cell volumes. The volume-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…The stagnantly pooled erythrocytes in the spleen could deplete their energy source, ATP, decrease intracellular pH and accelerate membrane lipid alteration [1]. It was previously reported that a decrease in pH accelerates osmotic fragility and activates volume decrease regulated by KCl co-transporter on red cell membrane from several animals in an in vitro condition [3,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stagnantly pooled erythrocytes in the spleen could deplete their energy source, ATP, decrease intracellular pH and accelerate membrane lipid alteration [1]. It was previously reported that a decrease in pH accelerates osmotic fragility and activates volume decrease regulated by KCl co-transporter on red cell membrane from several animals in an in vitro condition [3,12].…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory of Animal Physiology, Tokyo University of Agriculture, 1-1, Sakuragaoka 1 chome, Setagaya-ku Tokyo 156-8502, 2 Japan Livestock Technology Association, 9-20 Yushima 3 chome, Bunkyo-ku, Tokyo 113-0034 and 3 Equine Research Institute, Japan Racing Association, 321-4 Togami-cho, Utsunomiya, Tochigi 320-0856, Japan Boucher et al [1] suggested that osmotic fragility of the erythrocytes of racehorses was increased with exercise by the release of erythrocytes from the spleen into the circulation, whereas Smith et al [13] observed that exercise decreased the osmotic fragility of red cells. Hanzawa et al [7] reported that the frequent accumulation of erythrocytes in the spleen accelerated the membrane fragility in horses, and that heavy exercise increased red cell fragility for physical and chemical stresses, but light exercise decreased it, regardless of whether or not erythrocytes were released from the spleen into the circulation.…”
mentioning
confidence: 99%
“…K¤ influx was measured at 37°C by conventional radioactive tracer techniques using ÌÉRb¤ (DuPont-NEN, Bad Homburg, Germany) as a tracer for K¤ (Dunham & Ellory, 1981;Gibson, Ellory, Culliford & Fincham, 1993). Ouabain (final concentration, 100 ìÒ) was present in all experiments, obviating any K¤ influx through the Na¤,K¤-ATPase.…”
Section: K¤ Influxmentioning
confidence: 99%
“…ÌÉRb¤ (0·04-0·06 MBq ml¢ final) in 150 mÒ KCl or KNO× (final [K¤] = 7·5 mÒ) was added to the cell suspension and influx measured over 15 min, during which time uptake was linear. Fluxes were terminated and samples processed as described previously (Gibson et al 1993). Haematocrit was measured either by the cyanomethaemoglobin method or by microhaematocrit determination (Gibson et al 1993 …”
Section: K¤ Influxmentioning
confidence: 99%
See 1 more Smart Citation